SmartSwim: A novel approach to swimming analysis and coaching assistance based on wearable inertial sensors - Hamidi Rad, M. (École polytechnique fédérale de Lausanne, 2022)
As one of the three most popular sports in the Summer Olympics, competitive swimming has always been an attractive subject of study for sports scientists. The intricate nature of the swimmer's movements and the variety of techniques have led coaches to require analysis systems to gain a more detailed understanding of swimmers' performances, to plan training sessions as efficiently as possible and closely monitor the swimmer's progress. Surveys have shown that despite recent technological advances in sports, swimming coaches still need a measurement device that is accessible, easy to use, and provides easy-to-understand results. Conventional analysis systems such as high resolution cameras, while accurate, are too time consuming and cumbersome for daily use.